Development of Soccer Robot - Supaphon Kamon; Promphak Boonraksa; Sanit Teawchim (My University, 2024)
This paper presents the development of soccer robots for the WRG (World Robot Game) competition. Two models of soccer robots are designed and developed following the rules of WRG competition. One model is designed for 4WD (wheel drive), and another one is designed for 2WD. The soccer robots are controlled using a Flysky FS-GT3B RC transmitter in wireless communication. System structure and software development for controlling movement of the soccer robot are presented in this paper.
Keywords: Robotic Path Planning Algorithms